Noncompliance with the law prohibiting the sale of cigarettes to minors in Brazil: an inconvenient truth - André Salem Szklo; Tânia Maria Cavalcante (Jornal Brasileiro de Pneumologia, 2018)
ABSTRACT Objective: To draw up an up-to-date scenario of compliance with the law prohibiting the sale of cigarettes to minors. Methods: We used data about youth access to cigarette purchase that were obtained through a nationwide survey conducted in 2015 among students aged 13-17 years. We estimated simple proportions of attempts to buy cigarettes, success of attempts, purchase of cigarettes on a regular basis, and purchase of cigarettes on a regular basis in a store or bar. All estimates were stratified by gender, age group, and Brazilian macro-region. Crude absolute difference and adjusted absolute difference in the proportion of smokers in each category by variable of interest were analyzed by a generalized linear model with binomial distribution and identity link function. Results: Approximately 7 in every 10 adolescent smokers attempted to buy cigarettes at least once in the 30 days prior to the survey. Of those, approximately 9 in every 10 were successful, and individuals aged 16-17 years (vs. those aged 13-15 years) were less often prevented from buying cigarettes (adjusted absolute difference, 8.1%; p ≤ 0.05). Approximately 45% of all smokers aged 13-17 years in Brazil reported buying their own cigarettes on a regular basis without being prevented from doing so, and, of those, 80% reported buying them in a store or bar (vs. from a street vendor). Conclusions: Our findings raise an important public health concern and may contribute to supporting educational and surveillance measures to enforce compliance with existing anti-tobacco laws in Brazil, which have been disregarded.